Hubungan antara Motivasi Akademik dengan Active Procrastination di Masa Pandemi Covid-19 pada Siswa MAN 2 Tasikmalaya - Shanty Apriliani; Temi Damayanti Djamhoer (UNISBA Press, 2022)
Abstract. Based on the data, there is a phenomenon of procrastination among students in Indonesia during the Covid-19 pandemic. This procrastination is characterized by a tendency to often procrastinate tasks and obligations so that they accumulate at the end and many find it difficult to complete them. Although in general there is procrastination among students in Indonesia during the Covid-19 pandemic, students of MAN 2 Tasikmalaya still have a strong urge to take part in the distance learning process and have good academic achievements. Some researchers have revealed that adaptive procrastination has a positive effect on academic achievement. Adaptive procrastination or active procrastination is deliberate procrastination and for the most part leads to a satisfactory outcome. This study aims to determine how closely the relationship between academic motivation and active procrastination during the Covid-19 pandemic is for students at MAN 2 Tasikmalaya. The sample in this study were 311 students of MAN 2 Tasikmalaya. The measuring instrument for academic motivation uses the adaptation of the AMS (Academic Motivation Scale) based on the theory of Ryan & Deci, and the measuring instrument on the Active Procrastination Scale uses the adaptation of the APS (Active Procrastination Scale) based on the theory of Chun Chu & Choi. This study uses a quantitative approach with a correlational method. Data analysis using product moment pearson correlation test. The measurement results show that the correlation value is .642 > .111, which means that there is a strong and positive relationship between academic motivation and active procrastination. Abstrak. Berdasarkan data, terdapat fenomena prokrastinasi siswa di Indonesia pada masa pandemi Covid-19. Prokrastinasi ini ditandai dengan kecenderungan siswa yang sering menunda-nunda tugas dan kewajibannya sehingga menumpuk diakhir dan banyak yang merasa kesulitan dalam menyelesaikannya. Walaupun secara umum terjadi prokrastinasi pada siswa di Indonesia saat masa pandemi Covid-19, siswa MAN 2 Tasikmalaya tetap memiliki dorongan kuat untuk mengikuti proses pembelajaran jarak jauh dan mendapatkan prestasi akademik yang baik. Beberapa peneliti telah mengungkapkan bahwa penundaan yang adaptif memiliki efek positif pada prestasi akademik. Penundaan adaptif atau prokrastinasi aktif merupakan penundaan dengan sengaja dan sebagian besar mengarah pada hasil yang tetap memuaskan. Penelitian ini bertujuan untuk mengetahui seberapa erat hubungan antara motivasi akademik dengan active procrastination di masa pandemi Covid-19 pada siswa MAN 2 Tasikmalaya. Sampel dalam penelitian ini sebanyak 311 siswa MAN 2 Tasikmalaya. Alat ukur motivasi akademik menggunakan adaptasi AMS (Academic Motivation Scale) berdasarkan teori Ryan & Deci, dan alat ukur Active Procrastination Scale menggunakan adaptasi APS (Active Procrastination Scale) berdasarkan teori Chun Chu & Choi. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Analisis data menggunakan uji korelasi product moment pearson. Hasil pengukuran menunjukan bahwa nilai korelasi .642 > .111, yang berarti bahwa terdapat hubungan positif yang kuat antara motivasi akademik dengan active procrastination.